A sodium ion battery positive electrode material coated electrode and its preparation method and application
By using a hollow metal oxide to coat porous graphite and polyaniline layers in the cathode material of sodium-ion batteries, the problems of structural instability and poor conductivity of the cathode material during charging and discharging are solved, resulting in higher capacity and better cycle performance and rate performance.
Patent Information
- Application Number
- CN202411095165.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-12
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2044-08-12
AI Technical Summary
The crystal structure of existing sodium-ion battery cathode materials is prone to irreversible changes during charge and discharge, resulting in poor cycle performance and conductivity, which affects their application performance.
The active material of the positive electrode is a porous graphite and polyaniline layer coated with metal oxide. The metal oxide has a hollow structure and is coated with porous graphite and polyaniline to improve conductivity and structural stability. Polyaniline forms a conductive network as a conductive polymer, and porous graphite provides a large specific surface area and a void structure.
It improves the charge/discharge efficiency and capacity performance of sodium batteries, enhances the structural stability and conductivity of the cathode material, and improves cycle performance and rate performance.
Smart Images

Figure CN118645581B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of battery materials and relates to a sodium ion battery positive electrode material coated electrode. Background Art
[0002] With the in-depth research of new energy technologies, the continuous advancement of industrialization and the rapid development of social economy, the depletion of oil resources, global warming, environmental pollution and other problems have plagued modern society. People are eager to seek new clean renewable energy and energy storage materials and devices. In this context, lithium-ion batteries with high energy density, small size and long cycle life have developed rapidly and have shown great application prospects. However, the relatively scarce and unevenly distributed lithium resources have caused the cost of lithium-ion batteries in production and manufacturing to increase significantly, which is not conducive to the continued promotion and use of lithium batteries. In comparison, sodium resources are abundant and its physical and chemical properties are similar to those of lithium. Therefore, the development of high-performance sodium-ion batteries is of great significance for the vigorous development of clean energy.
[0003] The positive electrode material of sodium-ion batteries plays a decisive role in the energy density of batteries. Currently, the common positive electrode materials of sodium batteries mainly include polyanion compound materials, Prussian blue analogue materials, and oxide materials of transition metals and sodium. Relatively speaking, oxide materials of transition metals and sodium have higher specific capacity and working voltage, and are more suitable for the development of high-energy-density sodium-ion batteries. However, the crystal structure of such positive electrode materials is prone to irreversible changes during continuous charging and discharging, resulting in poor battery cycle performance. At the same time, the problem of poor conductivity will also cause the sodium battery rate performance to be unsatisfactory. Therefore, solving the volume change and conductivity problems of such positive electrode materials is the key to their further application in the field of sodium batteries.
[0004] CN118173762A discloses a sodium positive electrode material and a preparation method thereof, wherein the sodium positive electrode material comprises a core and a shell coated on the surface of the core; the core is a polycrystalline nickel-based layered oxide doped with an X element, wherein the X element is a metal element; the shell is a coating layer containing an F element; the sources of the X element and the F element are XF α The compound can reduce the side reaction with the electrolyte by doping with the X element in the core and coating with the F element, thereby improving the cycle performance; however, its cycle performance and rate performance need to be further improved.
[0005] CN118289729A discloses a sodium vanadium phosphate positive electrode material based on a porous coral structure induced by phosphomolybdic acid and a preparation method thereof. In the preparation process, a pentavalent vanadium source, a reducing agent, a sodium source and a phosphorus source are used as raw materials, phosphomolybdic acid is used as a morphology inducing agent, a sodium vanadium phosphate solid powder is prepared by a hydrothermal method, and a nitrogen-containing carbon source is wrapped and carbonized at high temperature to obtain a positive electrode material. The positive electrode material mainly has a porous coral-like structure and has a nitrogen-doped carbon coating layer on the outside, which effectively solves the problem of low energy density and improves the intrinsic electronic conductivity and ionic conductivity of the material, but its cycle performance and rate performance need to be further improved.
[0006] In order to solve the problems existing in the prior art, it is very necessary to develop a new positive electrode material for sodium ion batteries in this application. Summary of the invention
[0007] In view of the deficiencies in the prior art, the object of the present invention is to provide a sodium ion battery positive electrode material coated electrode and a preparation method and application thereof. The present invention uses a metal oxide coated porous graphite and polyaniline layer as the active material in the positive electrode material, wherein the metal oxide presents a hollow structure, which can not only expose more electrochemically active reaction sites and improve the charge and discharge efficiency of the sodium battery, but also a larger specific surface area is conducive to the deintercalation of sodium ions, thereby making the positive electrode material have a higher capacity performance, and the hollow structure can provide an inward buffer space for the volume expansion of the metal oxide during the charge and discharge process, which is conducive to the metal oxide maintaining structural stability; in addition, the presence of the surface-coated porous graphite and polyaniline can not only limit the volume expansion of the metal oxide, further improving the structural stability of the positive electrode material, but also the coating of the porous graphite and polyaniline can effectively improve the conductivity of the metal oxide, so that the positive electrode material exhibits more excellent cycle performance and rate performance.
[0008] To achieve this object, the present invention adopts the following technical solutions:
[0009] One of the purposes of the present invention is to provide a sodium ion battery positive electrode material coated electrode, the sodium ion battery positive electrode material coated electrode comprises a positive electrode current collector and a positive electrode material layer arranged on the surface of the positive electrode current collector; the present invention uses a metal oxide coated porous graphite and a polyaniline layer as an active material in the positive electrode material, wherein the metal oxide presents a hollow structure, which can not only expose more electrochemically active reaction sites, improve the charge and discharge efficiency of the sodium battery, but also a larger specific surface area is conducive to the deintercalation of sodium ions, thereby making the positive electrode material have a higher capacity performance; in addition, the hollow structure can provide an inward buffer space for the volume expansion of the metal oxide during the charge and discharge process, which is conducive to the metal oxide maintaining structural stability; in addition, the presence of the surface coated porous graphite and polyaniline can not only limit the volume expansion of the metal oxide, further improve the structural stability of the positive electrode material, but also the coating of the porous graphite and polyaniline can effectively improve the conductivity of the metal oxide, so that the positive electrode material exhibits more excellent cycle performance and rate performance.
[0010] The slurry used for the positive electrode material layer includes a positive electrode active material, a conductive agent and a binder;
[0011] The preparation method of the positive electrode active material comprises:
[0012] S1. Sodium nitrate, nickel nitrate and manganese nitrate are dissolved in deionized water at a molar ratio of (1.8-2.2):1:1 (e.g., 1.8:1:1, 1.9:1:1, 2:1:1, 2.1:1:1, 2.2:1:1, etc.), and then modified chitosan is added and ultrasonically treated at 65-75° C. (e.g., 65° C., 68° C., 70° C., 72° C., 75° C., etc.) to obtain a precursor;
[0013] S2, placing the precursor obtained in step S1 in a tube furnace, heating the precursor to 800-900°C (e.g., 800°C, 810°C, 820°C, 830°C, 840°C, 850°C, 860°C, 870°C, 880°C, 890°C, 900°C, etc.) at a heating rate of 1-10°C / min (e.g., 1°C / min, 2°C / min, 3°C / min, 4°C / min, 5°C / min, 6°C / min, 7°C / min, 8°C / min, 9°C / min, 10°C / min, etc.), and keeping the temperature for 12-24h (e.g., 12h, 14h, 16h, 18h, 20h, 22h, 24h, etc.) to obtain a matrix material;
[0014] S3, placing porous graphite, aniline monomer and the matrix material obtained in step S2 in a hydrochloric acid solution and mixing them, and then adding a hydrochloric acid solution of ammonium persulfate to react for 6-10 hours (for example, 6 hours, 7 hours, 8 hours, 9 hours, 10 hours, etc.), solid-liquid separation, and keeping the obtained solid at 600-800° C. (for example, 600° C., 620° C., 650° C., 680° C., 700° C., 720° C., 750° C., 770° C., 800° C., etc.) for 3-5 hours (for example, 3 hours, 3.5 hours, 4 hours, 4.5 hours, 5 hours, etc.) to obtain a positive electrode active material;
[0015] The preparation method of the modified chitosan comprises:
[0016] A1, add sodium hydroxide solution to the acetic acid solution of chitosan, react for 20-30 min (e.g., 20 min, 22 min, 24 min, 26 min, 28 min, 30 min, etc.) to obtain chitosan gel;
[0017] A2, reacting the chitosan gel obtained in step A1 with a glutaraldehyde solution for 20-30 min (e.g., 20 min, 22 min, 24 min, 26 min, 28 min, 30 min, etc.) to obtain cross-linked chitosan;
[0018] A3, reacting the cross-linked chitosan obtained in step A2 with the L-cysteine solution for 12-24 hours (e.g., 12 hours, 14 hours, 16 hours, 18 hours, 20 hours, 22 hours, 24 hours, etc.) to obtain substituted chitosan;
[0019] A4. Place the substituted chitosan obtained in step A3 in an aqueous inhibitor solution at 70-90°C (e.g., 70°C, 75°C, 80°C, 85°C, 90°C, etc.), stir to cause oil precipitation, until the substituted chitosan oil droplets are dispersed in water to obtain a mixed solution, then cool the mixed solution to 10-15°C (e.g., 10°C, 11°C, 12°C, 13°C, 14°C, 15°C, etc.) until solid particles appear, then add sodium stearate, and continue stirring for 3-10h (e.g., 3h, 4h, 5h, 6h, 7h, 8h, 9h, 10h, etc.) to obtain modified chitosan.
[0020] The present invention uses porous graphite and polyaniline layers coated with metal oxide as active materials in the positive electrode material, wherein the metal oxide presents a hollow structure, which can not only expose more electrochemically active reaction sites and improve the charge and discharge efficiency of the sodium battery, but also a larger specific surface area is conducive to the deintercalation of sodium ions, thereby making the positive electrode material have a higher capacity performance, and the hollow structure can provide an inward buffer space for the volume expansion of the metal oxide during the charge and discharge process, which is conducive to the metal oxide maintaining structural stability; in addition, the presence of the porous graphite and polyaniline coated on the surface can not only limit the volume expansion of the metal oxide, further improving the structural stability of the positive electrode material, but also the coating of the porous graphite and polyaniline can effectively improve the conductivity of the metal oxide, thereby making the positive electrode material show more excellent cycle performance and rate performance.
[0021] In the present invention, sodium nitrate, nickel nitrate and manganese nitrate will generate corresponding metal cations in aqueous solution. Since the modified chitosan is ionized in aqueous solution and exhibits electronegativity, there is electrostatic attraction between them. Meanwhile, a large number of thiol functional groups in the modified chitosan can produce complexing effect on metal ions. Therefore, under the dual effects of electrostatic action and complexing effect, a large number of metal cations will be densely packed on the surface of the modified chitosan and stably immobilized.
[0022] In the present invention, in order to better achieve the adsorption and fixation of metal particles by chitosan, crosslinking agent glutaraldehyde is used to crosslink chitosan through Schiff base reaction, and new active groups are introduced into the chitosan molecular chain, which not only improves the solubility of chitosan, but also increases the number of adsorption sites on the chitosan molecules, thereby increasing the adsorption efficiency of metal ions; sulfhydryl groups are introduced into chitosan molecules through L-cysteine, and spherical crystals are obtained through oil separation method, and the rich sulfhydryl groups and oxygen-containing functional groups on the surface of the chitosan spherical crystals make it have better adsorption capacity, so that the metal ions are adsorbed on the surface of the chitosan spherical crystals.
[0023] In the present invention, a porous graphite / polyaniline composite material layer is formed on the surface of a matrix material by in-situ polymerization, and the composite material layer prepared by the method can not only limit the volume expansion of metal oxides, further improve the structural stability of the positive electrode material, but also the coating of porous graphite and polyaniline can effectively improve the conductivity of metal oxides, so that the positive electrode material exhibits more excellent cycle performance and rate performance. Among them, polyaniline is introduced into the composite material layer, and polyaniline is a conductive polymer with excellent conductivity. It can be combined with carbon materials in the composite material as a conductive network to further increase the conductivity; porous graphite is selected as the carbon material in the composite material layer, which has a large specific surface area and a void structure, and can improve the energy density and cycle stability of the battery; polyaniline and porous carbon are subjected to high-temperature carbonization treatment, and polyaniline contains rich nitrogen. After high-temperature carbonization, nitrogen atoms will be doped into the carbon material to produce a large number of defects and active sites, further improving the electrochemical performance.
[0024] Preferably, the mass ratio of the positive electrode active material, the conductive agent and the binder is (8-8.5):1:(0.5-1), for example, 8:1:1, 8.1:1:0.9, 8.2:1:0.8, 8.3:1:0.7, 8.4:1:0.6, 8.5:1:0.5, etc.
[0025] Preferably, the conductive agent is conductive carbon black.
[0026] Preferably, the binder is polyvinylidene fluoride.
[0027] Preferably, the acetic acid solution of chitosan in step A1 is obtained by dissolving chitosan in acetic acid solution.
[0028] Preferably, based on 1 g of chitosan, the amount of acetic acid solution added is 30-40 mL, such as 30 mL, 32 mL, 35 mL, 38 mL, 40 mL, etc.
[0029] Preferably, the volume fraction of the acetic acid solution is 1-10%, for example, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%.
[0030] Preferably, based on 1 g of chitosan, the amount of sodium hydroxide solution added in step A1 is 1-2 g, such as 1 g, 1.2 g, 1.5 g, 1.8 g, 2 g, etc.
[0031] Preferably, the concentration of the sodium hydroxide solution in step A1 is 0.1-0.2 mol / L, for example, 0.1 mol / L, 0.12 mol / L, 0.15 mol / L, 0.18 mol / L, 0.2 mol / L, etc.
[0032] Preferably, the sodium hydroxide solution in step A1 is added dropwise.
[0033] Preferably, the step A1 further comprises standing, filtering and washing the mixture obtained after the reaction.
[0034] Preferably, the mass ratio of the chitosan gel in step A2 to glutaraldehyde in the glutaraldehyde solution is (1.5-2.5):1, for example, 1.5:1, 1.8:1, 2:1, 2.2:1, 2.5:1, etc.
[0035] Preferably, the concentration of the glutaraldehyde solution in step A2 is 2-3wt%, for example, 2wt%, 2.2wt%, 2.5wt%, 2.8wt%, 3wt%, etc.
[0036] Preferably, the step A2 further comprises standing, filtering and washing the mixture obtained after the reaction.
[0037] Preferably, the concentration of the L-cysteine solution in step A3 is 1-3wt%, for example, 1wt%, 1.2wt%, 1.5wt%, 1.8wt%, 2wt%, 2.2wt%, 2.5wt%, 2.8wt%, 3wt% and the like.
[0038] Preferably, the mass ratio of the cross-linked chitosan in step A3 to L-cysteine in the L-cysteine solution is 1:(1-2), for example 1:1, 1:1.1, 1:1.2, 1:1.3, 1:1.4, 1:1.5, 1:1.6, 1:1.7, 1:1.8, 1:1.9, 1:2, etc.
[0039] Preferably, the reaction in step A3 is a shaking reaction in a shaker, and the rotation speed of the shaker is 100-200 rpm, such as 100 rpm, 120 rpm, 150 rpm, 180 rpm, 200 rpm, etc.
[0040] Preferably, the inhibitor in the inhibitor aqueous solution in step A4 is any one of sodium chloride, potassium chloride, calcium chloride, sodium sulfate or potassium sulfate, or a combination of at least two thereof.
[0041] Preferably, the stirring rate in step A4 is 1-2 kW / m 3 , for example 1kW / m 3 , 1.2kW / m 3 , 1.4kW / m 3 , 1.6kW / m 3 , 1.8kW / m 3 , 2kW / m 3 wait.
[0042] Preferably, the cooling rate in step A4 is 2-10°C / min, for example, 2°C / min, 3°C / min, 4°C / min, 5°C / min, 6°C / min, 7°C / min, 8°C / min, 9°C / min, 10°C / min, etc.
[0043] Preferably, the amount of sodium stearate added in step A4 is 0.1-0.2% by mass of the mixed solution, for example 0.1%, 0.12%, 0.15%, 0.18%, 0.2%, etc.
[0044] Preferably, step A4 further comprises solid-liquid separation, washing and drying of the substance obtained after adding sodium stearate;
[0045] Preferably, the drying temperature is 25-55°C (for example, 25°C, 30°C, 35°C, 40°C, 45°C, 50°C, etc.), and the drying time is 12-48h (for example, 12h, 16h, 20h, 24h, 28h, 32h, 36h, 40h, 44h, 48h, etc.).
[0046] Preferably, based on the addition amount of porous graphite being 1 g, the addition amount of aniline monomer in step S3 is 1.5-2.5 g (for example, 1.5 g, 1.8 g, 2 g, 2.2 g, 2.5 g, etc.), and the addition amount of matrix material is 4-7 g (for example, 4 g, 4.5 g, 5 g, 5.5 g, 6 g, 6.5 g, 7 g, etc.).
[0047] Preferably, based on 0.1 mol of sodium nitrate, the amount of modified chitosan added in step S1 is 30-50 g, for example, 30 g, 32 g, 35 g, 38 g, 40 g, 42 g, 45 g, 48 g, 50 g, etc.
[0048] Preferably, the frequency of the ultrasound in step S1 is 100-200 KHz (for example, 100 KHz, 120 KHz, 150 KHz, 170 KHz, 200 KHz, etc.), and the time of ultrasound is 5-8 h (for example, 5 h, 6 h, 7 h, 8 h, etc.).
[0049] Preferably, the concentration of the hydrochloric acid solution in step S3 is 0.1-0.3 mol / L, for example, 0.1 mol / L, 0.15 mol / L, 0.2 mol / L, 0.25 mol / L, 0.3 mol / L, etc.
[0050] In step S3, the amount of ammonium persulfate added to the ammonium persulfate hydrochloric acid solution is 2-3 times the amount of aniline monomer added, for example, 2 times, 2.2 times, 2.5 times, 2.8 times, 3 times, etc.
[0051] The second object of the present invention is to provide a method for preparing a sodium ion battery positive electrode material coated electrode as described in the first object, the method for preparing a sodium ion battery positive electrode material coated electrode comprising:
[0052] (1) dissolving a binder in N-methylpyrrolidone, and then adding a positive electrode active material and a conductive agent to obtain a slurry;
[0053] (2) coating the slurry obtained in step (1) on the surface of the positive electrode collector and drying it to obtain a sodium ion battery positive electrode material coated electrode.
[0054] A third object of the present invention is to provide a sodium ion battery, comprising a positive electrode, a separator, an electrolyte and a negative electrode, wherein the positive electrode is the sodium ion battery positive electrode material coated electrode as described in one of the objects.
[0055] Compared with the prior art, the present invention has the following beneficial effects:
[0056] The present invention uses porous graphite and polyaniline layers coated with metal oxide as active materials in the positive electrode material, wherein the metal oxide presents a hollow structure, which can not only expose more electrochemically active reaction sites and improve the charge and discharge efficiency of the sodium battery, but also a larger specific surface area is conducive to the deintercalation of sodium ions, thereby making the positive electrode material have a higher capacity performance; and the hollow structure can provide an inward buffer space for the volume expansion of the metal oxide during the charge and discharge process, which is conducive to the metal oxide maintaining structural stability; in addition, the presence of the porous graphite and polyaniline coated on the surface can not only limit the volume expansion of the metal oxide, further improving the structural stability of the positive electrode material, but also the coating of the porous graphite and polyaniline can effectively improve the conductivity of the metal oxide, thereby making the positive electrode material show more excellent cycle performance and rate performance.
[0057] In the present invention, sodium nitrate, nickel nitrate and manganese nitrate will generate corresponding metal cations in aqueous solution. Since the modified chitosan is ionized in aqueous solution and exhibits electronegativity, there is electrostatic attraction between them. Meanwhile, a large number of thiol functional groups in the modified chitosan can produce complexing effect on metal ions. Therefore, under the dual effects of electrostatic action and complexing effect, a large number of metal cations will be densely packed on the surface of the modified chitosan and stably immobilized.
[0058] In the present invention, in order to better achieve the adsorption and fixation of metal particles by chitosan, crosslinking agent glutaraldehyde is used to crosslink chitosan through Schiff base reaction, and new active groups are introduced into the chitosan molecular chain, which not only improves the solubility of chitosan, but also increases the number of adsorption sites on the chitosan molecules, thereby increasing the adsorption efficiency of metal ions; sulfhydryl groups are introduced into chitosan molecules through L-cysteine, and spherical crystals are obtained through oil separation method, and the rich sulfhydryl groups and oxygen-containing functional groups on the surface of the chitosan spherical crystals make it have better adsorption capacity, so that the metal ions are adsorbed on the surface of the chitosan spherical crystals.
[0059] In the present invention, a porous graphite / polyaniline composite material layer is formed on the surface of a matrix material by in-situ polymerization, and the composite material layer prepared by the method can not only limit the volume expansion of metal oxides, further improve the structural stability of the positive electrode material, but also the coating of porous graphite and polyaniline can effectively improve the conductivity of metal oxides, so that the positive electrode material exhibits more excellent cycle performance and rate performance. Among them, polyaniline is introduced into the composite material layer, and polyaniline is a conductive polymer with excellent conductivity. It can be combined with carbon materials in the composite material as a conductive network to further increase the conductivity; porous graphite is selected as the carbon material in the composite material layer, which has a large specific surface area and a void structure, and can improve the energy density and cycle stability of the battery; polyaniline and porous carbon are subjected to high-temperature carbonization treatment, and polyaniline contains rich nitrogen. After high-temperature carbonization, nitrogen atoms will be doped into the carbon material to produce a large number of defects and active sites, further improving the electrochemical performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0060] Figure 1 A process flow chart of the preparation of the positive electrode active material provided in Example 1 of the present invention;
[0061] Figure 2 This is a scanning electron microscope image of the modified chitosan prepared in Example 1 of the present invention, with a scale of 200 nm;
[0062] Figure 3 This is a transmission electron microscope image of the matrix material prepared in Example 1 of the present invention, with a scale of 500 nm;
[0063] Figure 4 This is a scanning electron microscope image of the modified chitosan prepared in Example 2 of the present invention, with a scale of 200 nm. DETAILED DESCRIPTION
[0064] The technical solution of the present invention is described in detail below in conjunction with specific embodiments and their accompanying drawings. The embodiments recorded herein are specific embodiments of the present invention, which are used to illustrate the concept of the present invention; these descriptions are explanatory and exemplary and should not be construed as limitations on the embodiments of the present invention and the scope of protection of the present invention. In addition to the embodiments recorded herein, those skilled in the art can also adopt other obvious technical solutions based on the contents disclosed in the claims of this application and its specification, including technical solutions that adopt any obvious replacements and modifications to the embodiments recorded herein.
[0065] It should be noted that the chemical reagents used in the specific embodiments of the present invention are all commercially available products, and their brands and manufacturer information are as follows:
[0066] Chitosan: purchased from Xi'an Kangnuo Chemical Co., Ltd.; acetic acid solution, sodium hydroxide solution, glutaraldehyde, L-cysteine, sodium chloride, sodium stearate, manganese nitrate, ammonium persulfate: purchased from Merck Life Sciences Co., Ltd.; sodium nitrate: purchased from Runjing Chemical Co., Ltd.; nickel nitrate: purchased from Gaide Chemical Network; porous graphite: Qingdao Furuite Graphite Co., Ltd.; aniline monomer: purchased from Shanghai MacLean Biochemical Technology Co., Ltd.
[0067] Example 1
[0068] This embodiment provides a method for preparing a positive electrode active material, such as Figure 1 As shown, the preparation method comprises the following steps:
[0069] (1) dissolving chitosan in an acetic acid solution having a volume fraction of 7% to obtain a chitosan solution, wherein the ratio of chitosan to the acetic acid solution is 1 g:38 mL, and dropping a 0.18 mol / L sodium hydroxide solution into the chitosan solution, wherein the mass ratio of chitosan in the chitosan solution to sodium hydroxide in the sodium hydroxide solution is 1:1.8, and after the sodium hydroxide solution is completely dropped, stirring is continued for 28 minutes to react, and then the mixture is allowed to stand for 18 hours. After the standing period is over, the mixture is filtered and washed to obtain a chitosan gel;
[0070] (2) mixing the chitosan gel prepared in step (1) with a 2.8 wt % glutaraldehyde solution and stirring for 28 min to react, wherein the mass ratio of the chitosan gel to the glutaraldehyde in the glutaraldehyde solution is 2.2:1. After the reaction is completed, the mixture is allowed to stand for 42 h, and then filtered, washed and dried to obtain cross-linked chitosan;
[0071] (3) mixing the cross-linked chitosan prepared in step (2) with a 2.5 wt% L-cysteine solution, wherein the mass ratio of the cross-linked chitosan to the L-cysteine in the L-cysteine solution is 1:1.8, and placing the mixed solution in a shaker for 20 hours to react, the shaker speed is set to 180 rpm, and after the reaction is completed, the mixture is allowed to stand for 42 hours, and then filtered, washed and dried to obtain the substituted chitosan;
[0072] (4) 1 g of the substituted chitosan prepared in step (3) was placed in a 100 mL sodium chloride solution at 85° C. and a concentration of 0.003 g / mL, and stirred at a rate of 2 kW / m 3 The mixture was stirred under stirring conditions until oil precipitation occurred and the substituted chitosan oil droplets were uniformly dispersed in the water, and the temperature was cooled to 10°C at a cooling rate of 10°C / min until solid particles appeared, and then 0.1% of the mass of sodium stearate based on the mass of the mixed solution was added, and the stirring was continued for 5 hours to make the solid particles aggregate into compact spheres, which were filtered and dried at 25°C for 12 hours to obtain modified chitosan;
[0073] (5) 5 mL of a 0.1 mol / L sodium nitrate aqueous solution, 5 mL of a 0.05 mol / L nickel nitrate aqueous solution, and 5 mL of a 0.05 mol / L manganese nitrate aqueous solution were mixed uniformly to prepare a metal mixed solution, and then 0.25 g of the modified chitosan prepared in step (4) was added to the mixed solution, the temperature was controlled at 70° C., and an ultrasonic treatment was performed at an ultrasonic frequency of 100 kHz for 5 h, followed by solid-liquid separation to obtain a precursor;
[0074] (6) placing the precursor obtained in step (5) in a tube furnace, heating the temperature to 850° C. at a heating rate of 10° C. / min and maintaining the temperature for 24 h to obtain a matrix material;
[0075] (7) 0.1 g of porous graphite with an average particle size of 200-500 nm, 0.2 g of aniline monomer and 0.6 g of the matrix material obtained in step (6) were uniformly mixed in 50 mL of 0.1 mol / L hydrochloric acid to form a mixed solution, 0.6 g of ammonium persulfate was dissolved in 50 mL of 0.1 mol / L hydrochloric acid until it became transparent and colorless to form an ammonium persulfate solution, the mixed solution and the ammonium persulfate solution were mixed and reacted for 8 h, filtered to obtain a solid, and then the solid was heat treated at 700° C. for 4 h to obtain a positive electrode active material.
[0076] Figure 2 is a scanning electron microscope image of the modified chitosan obtained in step (4), Figure 2 It can be seen that the particles of modified chitosan are round and have an average particle size of 400-500 nm.
[0077] Figure 3is a transmission electron microscope image of the matrix material obtained in step (6), Figure 3 It can be seen that the core part of the material has a significantly higher transmittance than the shell part, so it is a hollow structure.
[0078] Example 2
[0079] This embodiment provides a method for preparing a positive electrode active material, the preparation method comprising the following steps:
[0080] (1) dissolving chitosan in an acetic acid solution having a volume fraction of 10% to obtain a chitosan solution, wherein the ratio of chitosan to the acetic acid solution is 1 g:30 mL, and dropping a 0.1 mol / L sodium hydroxide solution into the chitosan solution, wherein the mass ratio of chitosan in the chitosan solution to sodium hydroxide in the sodium hydroxide solution is 1:2, and after the sodium hydroxide solution is completely dropped, stirring is continued for 30 minutes to react, and then the mixture is allowed to stand for 12 hours. After the standing period is over, the mixture is filtered and washed to obtain a chitosan gel;
[0081] (2) mixing the chitosan gel prepared in step (1) with a 2 wt % glutaraldehyde solution and stirring for 30 min to react, wherein the mass ratio of the chitosan gel to the glutaraldehyde in the glutaraldehyde solution is 2.5:1. After the reaction is completed, the mixture is allowed to stand for 42 h, and then filtered, washed and dried to obtain cross-linked chitosan;
[0082] (3) mixing the cross-linked chitosan prepared in step (2) with a 3 wt % L-cysteine solution, wherein the mass ratio of the cross-linked chitosan to the L-cysteine in the L-cysteine solution is 1:2, and the mixed solution is placed in a shaker for 20 hours to react, the shaker speed is set to 200 rpm, and after the reaction is completed, the mixture is allowed to stand for 42 hours, and then filtered, washed and dried to obtain the substituted chitosan;
[0083] (4) 1 g of the substituted chitosan prepared in step (3) was placed in a 100 mL sodium chloride solution at 90° C. and a concentration of 0.005 g / mL, and stirred at a rate of 2 kW / m 3 The mixture was stirred under stirring conditions until oil precipitation occurred and the substituted chitosan oil droplets were uniformly dispersed in the water, and the temperature was cooled to 10°C at a cooling rate of 5°C / min until solid particles appeared, and then 0.2% of the mass of sodium stearate based on the mass of the mixed solution was added, and the stirring was continued for 10 hours to make the solid particles aggregate into compact spheres, which were filtered and dried at 25°C for 12 hours to obtain modified chitosan;
[0084] (5) 5 mL of a 0.11 mol / L sodium nitrate aqueous solution, 5 mL of a 0.05 mol / L nickel nitrate aqueous solution, and 5 mL of a 0.05 mol / L manganese nitrate aqueous solution were mixed uniformly to prepare a metal mixed solution, and then 0.25 g of the modified chitosan prepared in step (4) was added to the mixed solution, the temperature was controlled at 70° C., and an ultrasonic treatment was performed at an ultrasonic frequency of 150 kHz for 5 h, followed by solid-liquid separation to obtain a precursor;
[0085] (6) placing the precursor obtained in step (5) in a tube furnace, heating the temperature to 850° C. at a heating rate of 10° C. / min and maintaining the temperature for 24 h to obtain a matrix material;
[0086] (7) 0.1 g of porous graphite with an average particle size of 200-500 nm, 0.15 g of aniline monomer and 0.4 g of the matrix material obtained in step (6) were uniformly mixed in 50 mL of 0.3 mol / L hydrochloric acid to form a mixed solution, 0.3 g of ammonium persulfate was dissolved in 50 mL of 0.1 mol / L hydrochloric acid until it became transparent and colorless to form an ammonium persulfate solution, the mixed solution and the ammonium persulfate solution were mixed and reacted for 6 h, filtered to obtain a solid, and then the solid was heat treated at 600° C. for 5 h to obtain a positive electrode active material.
[0087] Figure 4 is a scanning electron microscope image of the modified chitosan obtained in step (4), Figure 4 It can be seen that the particles of modified chitosan are round and have an average particle size of 400-500 nm.
[0088] The matrix material obtained in this example was analyzed by transmission electron microscopy, and it was also found that the core part of the material had a significantly higher degree of transmission than the shell part, so it had a hollow structure.
[0089] Example 3
[0090] This embodiment provides a method for preparing a positive electrode active material, the preparation method comprising the following steps:
[0091] (1) dissolving chitosan in an acetic acid solution having a volume fraction of 5% to obtain a chitosan solution, wherein the ratio of chitosan to the acetic acid solution is 1 g:40 mL, and dropping a 0.1 mol / L sodium hydroxide solution into the chitosan solution, wherein the mass ratio of chitosan in the chitosan solution to sodium hydroxide in the sodium hydroxide solution is 1:1, and after the sodium hydroxide solution is completely dropped, stirring is continued for 20 minutes to react, and then the mixture is allowed to stand for 12 hours. After the standing period is over, the mixture is filtered and washed to obtain a chitosan gel;
[0092] (2) mixing the chitosan gel prepared in step (1) with a 3 wt % glutaraldehyde solution and stirring for 20 min to react, wherein the mass ratio of the chitosan gel to the glutaraldehyde in the glutaraldehyde solution is 1.5:1. After the reaction is completed, the mixture is allowed to stand for 42 h, and then filtered, washed and dried to obtain cross-linked chitosan;
[0093] (3) mixing the cross-linked chitosan prepared in step (2) with a 2 wt % L-cysteine solution, wherein the mass ratio of the cross-linked chitosan to the L-cysteine in the L-cysteine solution is 1:1.5, and placing the mixed solution in a shaker for 20 h to react, the shaker speed is set to 100 rpm, and after the reaction is completed, the mixture is allowed to stand for 42 h, and then filtered, washed and dried to obtain the substituted chitosan;
[0094] (4) 1 g of the substituted chitosan prepared in step (3) was placed in a 100 mL sodium chloride solution at 80° C. and a concentration of 0.001 g / mL, and stirred at a rate of 1 kW / m 3 The mixture was stirred under stirring conditions until oil precipitation occurred and the substituted chitosan oil droplets were uniformly dispersed in the water, and the temperature was cooled to 15°C at a cooling rate of 2°C / min until solid particles appeared, and then 0.15% of the mass of sodium stearate based on the mass of the mixed solution was added, and the stirring was continued for 10 hours to make the solid particles aggregate into compact spheres, which were filtered and dried at 40°C for 24 hours to obtain modified chitosan;
[0095] (5) 5 mL of a 0.11 mol / L sodium nitrate aqueous solution, 5 mL of a 0.05 mol / L nickel nitrate aqueous solution, and 5 mL of a 0.05 mol / L manganese nitrate aqueous solution were mixed uniformly to prepare a metal mixed solution, and then 0.2 g of the modified chitosan prepared in step (4) was added to the mixed solution, the temperature was controlled at 70° C., and ultrasonic treatment was performed at a frequency of 200 kHz for 6 h, followed by solid-liquid separation to obtain a precursor;
[0096] (6) placing the precursor obtained in step (5) in a tube furnace, heating the temperature to 800° C. at a heating rate of 2° C. / min and maintaining the temperature for 24 h to obtain a matrix material;
[0097] (7) 0.1 g of porous graphite with an average particle size of 200-500 nm, 0.25 g of aniline monomer and 0.7 g of the matrix material obtained in step (6) were uniformly mixed in 50 mL of 0.2 mol / L hydrochloric acid to form a mixed solution, 0.5 g of ammonium persulfate was dissolved in 50 mL of 0.1 mol / L hydrochloric acid until it became transparent and colorless to form an ammonium persulfate solution, the mixed solution and the ammonium persulfate solution were mixed and reacted for 6 h, filtered to obtain a solid, and then the solid was heat treated at 800° C. for 3 h to obtain a positive electrode active material.
[0098] Scanning electron microscopy analysis of the modified chitosan obtained in this example also revealed that the particles of the modified chitosan were round and had an average particle size of 400-500 nm.
[0099] The matrix material obtained in this example was analyzed by transmission electron microscopy, and it was also found that the core part of the material had a significantly higher degree of transmission than the shell part, so it had a hollow structure.
[0100] Example 4
[0101] This embodiment provides a method for preparing a positive electrode active material, the preparation method comprising the following steps:
[0102] (1) dissolving chitosan in an acetic acid solution having a volume fraction of 5% to obtain a chitosan solution, wherein the ratio of chitosan to the acetic acid solution is 1 g:38 mL, and dropping a 0.12 mol / L sodium hydroxide solution into the chitosan solution, wherein the mass ratio of chitosan in the chitosan solution to sodium hydroxide in the sodium hydroxide solution is 1:1, and after the sodium hydroxide solution is completely dropped, stirring is continued for 20 minutes to react, and then the mixture is allowed to stand for 12 hours. After the standing period is over, the mixture is filtered and washed to obtain a chitosan gel;
[0103] (2) mixing the chitosan gel prepared in step (1) with a 3 wt % glutaraldehyde solution and stirring for 22 min to react, wherein the mass ratio of the chitosan gel to the glutaraldehyde in the glutaraldehyde solution is 1.8:1. After the reaction is completed, the mixture is allowed to stand for 42 h, and then filtered, washed and dried to obtain cross-linked chitosan;
[0104] (3) mixing the cross-linked chitosan prepared in step (2) with a 2.5 wt% L-cysteine solution, wherein the mass ratio of the cross-linked chitosan to the L-cysteine in the L-cysteine solution is 1:1.8, and placing the mixed solution in a shaker for 20 hours to react, the shaker speed is set to 100 rpm, and after the reaction is completed, the mixture is allowed to stand for 42 hours, and then filtered, washed and dried to obtain the substituted chitosan;
[0105] (4) 1 g of the substituted chitosan prepared in step (3) was placed in a 100 mL sodium chloride solution at 88° C. and a concentration of 0.002 g / mL, and stirred at a rate of 1.2 kW / m 3 The mixture was stirred under stirring conditions until oil precipitation occurred and the substituted chitosan oil droplets were uniformly dispersed in the water, and the temperature was cooled to 15°C at a cooling rate of 6°C / min until solid particles appeared, and then 0.15% of the mass of sodium stearate based on the mass of the mixed solution was added, and the stirring was continued for 10 hours to make the solid particles aggregate into compact spheres, which were filtered and dried at 40°C for 24 hours to obtain modified chitosan;
[0106] (5) 5 mL of a 0.11 mol / L sodium nitrate aqueous solution, 5 mL of a 0.05 mol / L nickel nitrate aqueous solution, and 5 mL of a 0.05 mol / L manganese nitrate aqueous solution were mixed uniformly to prepare a metal mixed solution, and then 0.2 g of the modified chitosan prepared in step (4) was added to the mixed solution, the temperature was controlled at 70° C., and an ultrasonic treatment was performed at an ultrasonic frequency of 150 kHz for 6 h, followed by solid-liquid separation to obtain a precursor;
[0107] (6) placing the precursor obtained in step (5) in a tube furnace, heating the temperature to 820° C. at a heating rate of 1° C. / min and maintaining the temperature for 16 h to obtain a matrix material;
[0108] (7) 0.1 g of porous graphite with an average particle size of 200-500 nm, 0.25 g of aniline monomer and 0.7 g of the matrix material obtained in step (6) were uniformly mixed in 50 mL of 0.2 mol / L hydrochloric acid to form a mixed solution, 0.5 g of ammonium persulfate was dissolved in 50 mL of 0.1 mol / L hydrochloric acid until it became transparent and colorless to form an ammonium persulfate solution, the mixed solution and the ammonium persulfate solution were mixed and reacted for 6 h, filtered to obtain a solid, and then the solid was heat treated at 650° C. for 4.5 h to obtain a positive electrode active material.
[0109] Scanning electron microscopy analysis of the modified chitosan obtained in this example also revealed that the particles of the modified chitosan were round and had an average particle size of 400-500 nm.
[0110] The matrix material obtained in this example was analyzed by transmission electron microscopy, and it was also found that the core part of the material had a significantly higher degree of transmission than the shell part, so it had a hollow structure.
[0111] Comparative Example 1
[0112] The difference from Example 1 is that step (2) is not included, that is, the chitosan gel is not cross-linked, and the rest of the preparation method is the same as that of Example 1.
[0113] Comparative Example 2
[0114] The difference from Example 1 is that step (3) is not included, that is, the chitosan is not subjected to thiol substitution, and the rest of the preparation method is the same as that of Example 1.
[0115] Comparative Example 3
[0116] The difference from Example 1 is that step (4) is not included, that is, the chitosan is not subjected to spherical treatment, and the rest of the preparation method is the same as that of Example 1.
[0117] Comparative Example 4
[0118] The difference from Example 1 is that step (7) is not included, that is, the base material is not coated, and the rest of the preparation method is the same as that of Example 1.
[0119] Comparative Example 5
[0120] The difference from Example 1 is that step (7) does not include porous graphite, and the rest of the preparation method is the same as that of Example 1.
[0121] Comparative Example 6
[0122] The difference from Example 1 is that step (7) does not include aniline monomer, and the rest of the preparation method is the same as that of Example 1.
[0123] Application Examples
[0124] (1) 5 g of polyvinylidene fluoride was dissolved in N-methylpyrrolidone, and then 85 g of the positive electrode active material prepared in Examples 1-4 and Comparative Examples 1-6 and 10 g of conductive carbon black were added to form a mixed solution, and the stirring rate was controlled to be 1000 r / min to form a composite slurry;
[0125] (2) coating the composite slurry obtained in step (1) onto the surface of aluminum foil, and drying the composite slurry to form a coated electrode;
[0126] (3) The coated electrode obtained in step (2) was used as a positive electrode, a sodium metal sheet as a negative electrode, a glass fiber mesh as a separator, and a concentration of 1 mol / L NaClO4 / (ethylene carbonate and dimethyl carbonate in a volume ratio of 1:1) as an electrolyte. A button cell was assembled in a glove box and the following electrochemical performance test was performed. The test method was based on TCIAPS0031-2023 "General Specification for Sodium Ion Batteries". The specific capacity and cycle stability test results at a current density of 0.1C are shown in Table 1, and the discharge specific capacity test results are shown in Table 2:
[0127] Table 1 Specific capacity and cycle stability test results
[0128]
[0129] Table 2 Discharge specific capacity test results
[0130]
[0131] It can be seen from the test results of Examples 1-4 that the battery prepared by using the specific positive electrode active material of the present application has good cycle performance and rate performance; the reason is that: the metal oxide inside the positive electrode active material is a hollow structure, which can expose more electrochemically active reaction sites, can improve the charge and discharge efficiency of sodium ions, and at the same time has a larger specific surface area that is conducive to the deintercalation of sodium ions, so that the positive electrode material has a higher capacity performance, and the hollow structure can also provide an inward buffer space for the volume expansion of the metal oxide during the charge and discharge process, which is conducive to maintaining the stability of the structure; the presence of the surface-coated porous graphite and polyaniline can further limit the expansion of the metal oxide system, thereby improving the stability of the structure, and the coordinated effect of polyaniline and porous graphite can further increase the conductivity of the metal oxide, thereby further improving the cycle performance and rate performance.
[0132] By comparing Example 1 and Comparative Example 1, it can be seen that when the chitosan gel is not cross-linked, new active groups cannot be introduced into the chitosan molecular chain, which is not conducive to increasing the number of adsorption sites on the molecule, which is not conducive to the formation of a hollow structure, which will greatly affect the charge and discharge efficiency of sodium ions, and is not conducive to the deintercalation of sodium ions, which is not conducive to the improvement of the capacity of the positive electrode material and the maintenance of the structural stability, thereby affecting the cycle performance and rate performance of the battery.
[0133] By comparing Example 1 and Comparative Example 2, it can be seen that when the thiol group of chitosan is not replaced, the adsorption effect of metal ions will be poor, and the effect of hollow structure formation will be poor, which will affect the charge and discharge efficiency of sodium ions and be unfavorable for the deintercalation of sodium ions, thereby affecting the cycle performance and rate performance of the battery.
[0134] By comparing Example 1 and Comparative Example 3, it can be seen that if chitosan is not sphericalized, the formation of the hollow structure will be affected, thereby affecting the charge and discharge efficiency of sodium ions, and is not conducive to the deintercalation of sodium ions, thereby affecting the cycle performance and rate performance of the battery.
[0135] By comparing Example 1 and Comparative Example 4, it can be seen that when the base material is not coated, the volume expansion effect of the metal material during the charge and discharge process will be deteriorated, and the metal ions will be easily dissolved and react with the electrolyte, which is not conducive to the performance of the battery's conductive properties, thereby affecting the battery's cycle performance and rate performance.
[0136] By comparing Example 1 with Comparative Examples 5-6, it can be seen that when only any one of porous graphite or polyaniline is used to coat the base material, the conductivity will deteriorate, thereby affecting the cycle performance and rate performance of the battery.
[0137] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.
Claims
1. A sodium ion battery positive electrode material coated electrode, characterized in that: The sodium ion battery positive electrode material coated electrode comprises a positive electrode current collector and a positive electrode material layer arranged on the surface of the positive electrode current collector; The slurry used for the positive electrode material layer includes a positive electrode active material, a conductive agent and a binder; The preparation method of the positive electrode active material comprises: S1. Sodium nitrate, nickel nitrate and manganese nitrate are dissolved in deionized water at a molar ratio of (1.8-2.2):1:1, and then modified chitosan is added and ultrasonically treated at 65-75° C. to obtain a precursor; S2, placing the precursor obtained in step S1 in a tube furnace, heating it to 800-900°C at a heating rate of 1-10°C / min and keeping it at that temperature for 12-24 h to obtain a matrix material; S3, placing the porous graphite, the aniline monomer and the matrix material obtained in step S2 in a hydrochloric acid solution and mixing them, then adding a hydrochloric acid solution of ammonium persulfate to react for 6-10 hours, separating the solid and the liquid, and keeping the obtained solid at 600-800° C. for 3-5 hours to obtain a positive electrode active material; The preparation method of the modified chitosan comprises: A1. Add sodium hydroxide solution to the acetic acid solution of chitosan and react for 20-30 min to obtain chitosan gel; A2, reacting the chitosan gel obtained in step A1 with glutaraldehyde solution for 20-30 min to obtain cross-linked chitosan; A3, reacting the cross-linked chitosan obtained in step A2 with L-cysteine solution for 12-24 h to obtain substituted chitosan; A4, placing the substituted chitosan obtained in step A3 in an inhibitor aqueous solution at 70-90°C, stirring to cause oil precipitation, until the substituted chitosan oil droplets are dispersed in water to obtain a mixed solution, then cooling the mixed solution to 10-15°C until solid particles appear, then adding sodium stearate, and continuing stirring for 3-10 hours to obtain modified chitosan; The inhibitor in the inhibitor aqueous solution of step A4 is any one of sodium chloride, potassium chloride, calcium chloride, sodium sulfate or potassium sulfate, or a combination of at least two thereof.
2. The sodium ion battery positive electrode material coated electrode according to claim 1, characterized in that: The mass ratio of the positive electrode active material, the conductive agent and the binder is (8-8.5):1:(0.5-1); The conductive agent is conductive carbon black; The binder is polyvinylidene fluoride.
3. The sodium ion battery positive electrode material coated electrode according to claim 1, characterized in that: The chitosan acetic acid solution in step A1 is obtained by dissolving chitosan in acetic acid solution; Based on the addition amount of chitosan being 1 g, the addition amount of the acetic acid solution is 30-40 mL; The volume fraction of the acetic acid solution is 1-10%; Based on the addition amount of chitosan being 1 g, the addition amount of sodium hydroxide in the sodium hydroxide solution in step A1 is 1-2 g; The concentration of the sodium hydroxide solution in step A1 is 0.1-0.2 mol / L; The sodium hydroxide solution in step A1 is added dropwise; The step A1 further comprises allowing the mixture obtained after the reaction to stand, filtering and washing.
4. The sodium ion battery positive electrode material coated electrode according to claim 1, characterized in that: The mass ratio of the chitosan gel in step A2 to the glutaraldehyde in the glutaraldehyde solution is (1.5-2.5):1; The concentration of the glutaraldehyde solution in step A2 is 2-3wt%; The step A2 further comprises allowing the mixture obtained after the reaction to stand, filtering and washing.
5. The sodium ion battery positive electrode material coated electrode according to claim 1, characterized in that: The concentration of the L-cysteine solution in step A3 is 1-3 wt %; The mass ratio of the cross-linked chitosan in step A3 to the L-cysteine in the L-cysteine solution is 1:(1-2); The reaction in step A3 is carried out by shaking in a shaker at a rotation speed of 100-200 rpm.
6. The sodium ion battery positive electrode material coated electrode according to claim 1, characterized in that: The stirring rate in step A4 is 1-2 kW / m 3 ; The cooling rate in step A4 is 2-10°C / min; The amount of sodium stearate added in step A4 is 0.1-0.2% by mass of the mixed solution; Step A4 further comprises performing solid-liquid separation, washing and drying on the substance obtained after adding sodium stearate; The drying temperature is 25-55° C. and the drying time is 12-48 h.
7. The sodium ion battery positive electrode material coated electrode according to claim 1, characterized in that: Based on the addition amount of sodium nitrate being 0.1 mol, the addition amount of the modified chitosan in step S1 is 30-50 g; The ultrasound frequency in step S1 is 100-200 KHz, and the ultrasound time is 5-8 h.
8. The sodium ion battery positive electrode material coated electrode according to claim 1, characterized in that: Based on the addition amount of porous graphite being 1 g, the addition amount of aniline monomer in step S3 is 1.5-2.5 g, and the addition amount of matrix material is 4-7 g; The concentration of the hydrochloric acid solution in step S3 is 0.1-0.3 mol / L; In step S3, the amount of ammonium persulfate added to the ammonium persulfate hydrochloric acid solution is 2-3 times the amount of aniline monomer added.
9. The method for preparing a sodium ion battery positive electrode material coated electrode according to any one of claims 1 to 8, characterized in that: The method for preparing the sodium ion battery positive electrode material coated electrode comprises: (1) dissolving a binder in N-methylpyrrolidone, and then adding a positive electrode active material and a conductive agent to obtain a slurry; (2) The slurry obtained in step (1) is coated on the surface of the positive electrode current collector and dried to obtain a sodium ion battery positive electrode material coated electrode.
10. A sodium ion battery, characterized in that: The sodium ion battery comprises a positive electrode, a separator, an electrolyte and a negative electrode, wherein the positive electrode is an electrode coated with a positive electrode material of a sodium ion battery according to any one of claims 1 to 8.
Citation Information
Patent Citations
Sodium-ion battery positive electrode material, preparation method thereof and sodium-ion battery
CN118173762A
Ni@N-C composite cathode material, preparation method thereof, and application of same in lithium-air batteries
CN107293730A
Preparation method of high-strength carbon-coated aluminum foil current collector for lithium battery
CN118016897A